Acceso libre a las publicaciones y jerarquía de la credibilidad - Wulff Barreiro, Enrique (Revista General de Información y Documentación, 2010)
The scientific journal and scientific paper reconfiguration inside the new prices model transition emphasize a change that opens up the open access environment. With the opening of new managerial chronologies. In the open space authority editors, librarians and authors explain, in the disparity, the responsibility and the models of the information sources. A sustainable and profitable industry search for the kind of interaction that is necessary to the full understanding of the problem. The uneasy relationship between the oceanographic and fisheries problems, its insularity, is a case of variation of the degree of integration that is well exemplified by the "closeness" between the free of charge electronic publications and the costs of the paper publications.
Keywords: Open access; Politics of information; Scientific journals; Marine sciences; Internet; Aquaculture; Fisheries